USER EXPERIENCE AUDIT OF THREE POPULAR LANGUAGE LEARNING APPS: A HEURISTIC EVALUATION OF DUOLINGO, BABBEL, AND ELSA SPEAK - Siti Annisa Dahlan (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2026)
Mobile-Assisted Language Learning (MALL) applications are among the most widely downloaded educational tools globally, yet rigorous usability evaluations using validated pedagogical frameworks remain scarce. This study applies a multi-evaluator heuristic protocol to three commercially dominant platforms, namely Duolingo, Babbel, and ELSA Speak, combining Nielsen’s (1994) 10 Usability Heuristics with an original Pedagogical Usability framework that connects interface design to second language acquisition (SLA) theory. Three evaluators with complementary expertise in EFL pedagogy and software development independently assessed each application on identical Android devices; inter-evaluator agreement was measured using Cohen’s Kappa, and disagreements were resolved through structured consensus. The consensus evaluation identified 19 usability issues (Duolingo: 7; Babbel: 7; ELSA Speak: 5) and 14 confirmed strengths; 42% (n = 8) were classified as Major (Severity 3). Inter-rater agreement was Substantial (κ = 0.769, pooled; p < .001). Heuristic 4 (Consistency and Standards) was the sole universal strength; Heuristic 9 (Error Recognition and Recovery) showed the greatest pedagogical variance. No application demonstrated universal usability superiority; monetization constraints represent the primary systemic source of usability pedagogy conflict. All findings are expert-based inferences and do not directly measure learner outcomes; empirical validation with learner participants is recommended.